Phenomenalism and Kant - de Sá Pereira, Roberto Horacio (Con-Textos Kantianos. International Journal of Philosophy, 2021)
Readings of Kant’s Critique as endorsing phenomenalism have occupied the spotlight in recent times: ontological phenomenalism, semantic phenomenalism, analytical phenomenalism, epistemological phenomenalism, and so on. Yet, they raise the same old coherence problem with the Critique: are they compatible with Kant’s Refutation of Idealism? Are they able to reconcile the Fourth Paralogism of the first edition with the Refutation of the second, since Kant repeatedly claimed that he never changed his mind in-between the two editions of his Critique? This paper addresses the key question: was Kant a phenomenalist and, if he was, in which precise sense? I propose a metaphysical but not ontologically reductionist reading of Kant as a phenomenalist. I argue for the following claims. To be sure, for Kant appearance is mere representation. Yet, appearance is representation only insofar as we take “appearance” in the empirical sense, namely the way that the mind-independent existing noumenon appears in space and, crucially, when we take “representation” in the transcendental sense, namely the mind-dependent way that we can cognize the same mind-independent existing noumenon. How shall I argue in defense of my alternative reading? First, I argue that my reading is pretty much compatible with Kant’s Refutation (in contrast to the rivals). Second, I argue that my reading reconciles the causal with the intentional readings of the Refutation. Third, I argue that my reading makes the Fourth Paralogism of the first edition and the Refutation of Idealism of the second completely compatible.